Business process management : 15th International Conference, BPM 2017, Barcelona, Spain, September 10-15, 2017, Proceedings /: 15th International Conference, BPM 2017, Barcelona, Spain, September 10-15, 2017, Proceedings. (2017) - Unknown
No abstract available